Validation of Illicium × rubellum (Schisandraceae), a natural hybrid from Taiwan - Huang, Wei-Jie; Chung, Shih-Wen (Phytotaxa, 2023)
Illicium × rubellum nom. nud. was proposed based on a single individual without description and indication of type. In this paper we report two additional populations of this hybrid found in Taiwan. The morphology of leaf and flower is intermediate between I. arborescens and I. anisatum. Molecular data from ITS sequence of nuclear ribosomal DNA also suggests its hybrid origin. Here we validate this name with a formal description and type designation. This is the first report of natural hybrid species in Illicium and Schisandraceae. Detailed morphology comparison and illustrations are also provided.